Do, do, do, do you remember? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
five-day regional seminar held in Trinidad and Tobago in September 2000, about farmer participation in training in ecological crop management, including integrated pest management (IPM)